Anestezjologia i intensywna terapia Coronary artery bypass grafting in abciximab: treated non-elective patients - Drwiła, Rafał; Ziętkiewicz, Marcin; Plitzner, Dariusz; Kapelak, Bogusław; Wróbel, Krzysztof; Moncznik, Paweł; Śnieżek-Maciejewska, Maria; Sadowski, Jerzy; Andres, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Between January 2002 and September 2005 abciximab was used in 1150 patients with a wide spectrum of cardiological interventions in our haemodynamic department. Among them 48 were operated on for cardiopulmonary bypass (CPB). 12 were operated on in non-elective mode not later than 14 days after abciximab use. Material and methods: The group of 12 patients operated on in non-elective mode during which the potential effect of abciximab was compared with the group of 80 coronary patients operated on also non-electively. Both groups received heparin and aspirin during the preoperative period. We analyzed postoperative drainage and use of blood and blood products. Results: Blood loss and transfusions of packed red cells and fresh frozen plasma were similar in both groups. The volume of transfused platelets was higher in the abciximab-treated group (p<0.01). Conclusions: Risk of post-operative bleeding is similar in non-elective patients receiving heparin/aspirin after abciximab compared to the group treated with heparin/aspirin alone. There is still no gold-standard test for platelet function assessment available.